2019
DOI: 10.1002/ejhf.1608
|View full text |Cite
|
Sign up to set email alerts
|

Plasma proteomic approach in patients with heart failure: insights into pathogenesis of disease progression and potential novel treatment targets

Abstract: Aims To provide insights into pathogenesis of disease progression and potential novel treatment targets for patients with heart failure by investigation of the plasma proteome using network analysis. Methods and results The plasma proteome of 50 patients with heart failure who died or were rehospitalised were compared with 50 patients with heart failure, matched for age and sex, who did not have an event. Peptides were analysed on two‐dimensional liquid chromatography coupled to tandem mass spectrometry (2D LC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…A recent study demonstrated that glutathione, arginine and proline, and pyruvate pathways were activated in HF patients who died or were rehospitalized. 249 The ubiquitous lysosomal protease cathepsin D is secreted as a response to oxidative stress, but its role in HF was unknown. It has been recently discovered that elevated levels of cathepsin D are associated with HF severity and poor outcome.…”
Section: Novel Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study demonstrated that glutathione, arginine and proline, and pyruvate pathways were activated in HF patients who died or were rehospitalized. 249 The ubiquitous lysosomal protease cathepsin D is secreted as a response to oxidative stress, but its role in HF was unknown. It has been recently discovered that elevated levels of cathepsin D are associated with HF severity and poor outcome.…”
Section: Novel Perspectivesmentioning
confidence: 99%
“…Proteomic processes also represent a field of interest and could be targets for the future. A recent study demonstrated that glutathione, arginine and proline, and pyruvate pathways were activated in HF patients who died or were rehospitalized 249 . The ubiquitous lysosomal protease cathepsin D is secreted as a response to oxidative stress, but its role in HF was unknown.…”
Section: Novel Perspectivesmentioning
confidence: 99%
“…The plasma proteome of HF patients has been analyzed extensively to identify biomarkers for HF and their genetic risk-association as well as to understand organ crosstalk via blood stream [ 99 101 ]. Egerstedt et al studied the plasma proteome of HF patients in different clinical stages (early HF development, manifest advanced HF, and reversal of HF after heart transplantation) [ 102 ••].…”
Section: Omics In Heart Failurementioning
confidence: 99%
“…Several studies have examined MS/MS proteomics to evaluate the disease state of HF ( 9 , 44 , 45 , 46 , 47 ). In a study of ischemic cardiomyopathy (ICM), Yi et al.…”
Section: Current Use Of Proteomics In Hf Studiesmentioning
confidence: 99%
“…The assessment of proteins expressed in a specific state and how these proteins might change over time and with alterations in disease circumstance are notable. Such “proteomics” may reveal previously unrecognized pathophysiological pathways in HF and solidify understanding of the inter-relatedness of known processes ( 9 ). Proteomics allows for testing of thousands of proteins simultaneously, using as little as 1 μl of a sample ( 10 ), which permits rapid and high-throughput discovery of potential biomarkers of HF or identifies druggable targets, thus rapidly translating findings from bench to bedside.…”
mentioning
confidence: 99%